DECODING THE RISK PROFILE OF NON-ALCOHOLIC FATTY LIVER DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS - BABU RAJENDRA PRASAD TR,; LEENA JOSE,; JAYAKRISHNAN KS,; ANIKET KUMAR,; HAMEED, JAMILA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This is a systematic review and meta-analysis that aims to evaluate the prevalence of non-alcoholic fatty liver disease (NAFLD) and the risk factors such as type 2 diabetes mellitus (T2DM), hypertension, obesity, PCOS, and sleep apnea associated with it. NAFLD is one of the most prevalent diseases that affect approximately 40% of diabetic, hypertensive, dyslipidemic obese individuals. Its asymptomatic nature often leads to under diagnosis and progress to severe liver cirrhosis and hepatocellular carcinoma. Methods: A total of 1819 studies from database from 2019 to 2024 were identified, finally 10 studies were selected, the Statistical Package for the Social Sciences software was used for data analysis. Results: The analyses across different geographic regions with 620,3969 patients with NAFLD, T2DM prevalence came out to be 15% among males, whereas 22.2% in females. A prevalence of 52.55% was noted in the obese population and 26.74% in lean individuals, with PCOS 43%, metabolic syndrome 75.3%, and sleep apnea 40% and various risk factors were also identified. Conclusion: This review throws light on the nature of NAFLD, focusing on the need for increased awareness and screening among people at risk, strategies could help avert liver disease progression.